Genetic Analysis of Two Sympatric Sea Urchins from Genus Diadema (Echinodermata: Echinoidea: Diadematidae) from Malaysian Borneo - Nursyuhaida, Md Shahid; Raymie, Nurhassan; Siti Akmar Khadijah, Ab Rahim; Ruhana, Hassan (Universiti Malaysia Sarawak (UNIMAS), 2015)
Genus Diadema (Echinoidea: Diadematidae) has been reported to be the most widespread and ecologically important shallow water tropical sea urchins. Morphological variations and species distributions are complicated to elucidate due to complexity in making reliable identifications. Genus Diadema had involved in many debates, particularly on the mode of speciation and the specific status of Diadema setosum and Diadema savignyi. Therefore, relationships among Diadema species found in Malaysian Borneo have been examined using 16S rRNA gene analysis. Monophyletic clade of genus Diadema with respect to the outgroup was obtained with high bootstrap values of 100% (MP), 100% (NJ), 100% (ML) and Bayesian Posterior Probability is equal to 1.00. Two monophyletic clades were apparent separating D. setosum (Clade I) and D. savignyi (Clade II), with strong support of 100% (MP), 100% (NJ), 80% (ML) and Bayesian Posterior Probability is equal to 1.00. In addition, high genetic variation among species had been recorded (9.85%), suggesting that D. setosum and D. savignyi are two distinct entities. Furthermore, D. setosum and D. savignyi are sympatric species based on their distribution and overlapping ranges in Malaysian Borneo.